Preparation method and application of wear-resistant light zinc-based composite material containing special grain refiner
By using modified silicon carbide reinforcement and modified cerium oxide grain refiner, the problems of uneven dispersion and poor bonding in zinc-based composite materials have been solved, enabling the preparation of high-strength, wear-resistant and corrosion-resistant zinc-based composite materials, which are suitable for aerospace, automotive manufacturing and biomedical materials and other fields.
Patent Information
- Application Number
- CN202511124585.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-12
- Publication Date
- 2025-11-07
AI Technical Summary
Existing nanoscale refining agents and reinforcing phases are unevenly dispersed in zinc-based composite materials and poorly bonded to the matrix, affecting the uniformity and reliability of the materials and making it difficult to meet the wear resistance and mechanical performance requirements of high-end applications.
By using modified silicon carbide reinforcement and modified cerium oxide grain refiner, and through plasma activation and silane grafting modification treatment, the dispersibility and wettability are improved, and the grain structure is optimized through cumulative rolling process to form a zinc-based composite material with high strength and good wear resistance.
It significantly improves the tensile strength, hardness, wear resistance and corrosion resistance of zinc-based composite materials, optimizes grain refinement, reduces stress concentration, and maintains the material's lightweight advantage.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of zinc-based composite materials, in particular to a preparation method of wear-resistant lightweight zinc-based composite material containing special grain refiner and application thereof. BACKGROUND
[0002] In the current field of material science, zinc-based composite materials have attracted widespread attention due to their lightweight and good processing performance. However, their wear resistance and mechanical properties often fail to meet the needs of high-end applications. The traditional zinc alloy has a relatively rough grain structure, which leads to insufficient material strength and wear resistance, limiting its application potential in the fields of aerospace, automobile manufacturing, and biomedical materials. To overcome these problems, researchers have been working on developing efficient grain refiners and reinforcement phase addition technologies in order to improve the overall performance of zinc-based materials by refining the grain structure and optimizing the microstructure.
[0003] Existing nanoscale refiners and reinforcement phases often face problems such as uneven dispersion and poor bonding with the matrix, which to some extent affects the uniformity and reliability of the material. In view of this, we propose a preparation method of wear-resistant lightweight zinc-based composite material containing special grain refiner and application thereof. SUMMARY
[0004] The present application aims to provide a preparation method of wear-resistant lightweight zinc-based composite material containing special grain refiner and application thereof, to solve the problem of uneven dispersion and poor bonding with the matrix of existing nanoscale refiners and reinforcement phases, which to some extent affects the uniformity and reliability of the material.
[0005] In one aspect, the present application provides a preparation method of wear-resistant lightweight zinc-based composite material containing special grain refiner, comprising the following steps: S1.1, respectively take the following raw materials: zinc alloy, modified silicon carbide reinforcement, modified cerium oxide grain refiner, and sodium chloride-potassium chloride composite flux; S1.2, place the zinc alloy in a graphite crucible, add the sodium chloride-potassium chloride composite flux, and introduce argon gas. The temperature is raised to 550-560℃ and maintained. Stir at a speed of 150-200rpm for 10-15min to form a melt; S1.3, ultrasonically disperse the modified cerium oxide grain refiner into the melt at a power of 1.0-1.2kW; maintain the melt temperature at 545-555℃, add the dried modified silicon carbide reinforcement, and stir at a speed of 600-800rpm for 20-30min to obtain a mixed material; S1.4, when the temperature of the mixed material drops to 460-480℃, casting is carried out by using a pressure of 60-80MPa; then, through accumulative roll bonding, after rolling, cooling to room temperature, and annealing at 300℃ for 20min, a wear-resistant lightweight zinc-based composite material containing a special grain refiner is obtained.
[0006] As preferred, in S1.1, the following raw materials are weighed by weight parts: zinc alloy 80-100 parts by weight, modified silicon carbide reinforcing agent 8-15 parts by weight, modified cerium oxide grain refiner 0.5-1.0 parts by weight, and sodium chloride-potassium chloride flux 0.5-1.5 parts by weight.
[0007] As preferred, in S1.2, the flow rate of argon is 3-5L / min; the temperature is raised at a rate of 8-10℃ / min.
[0008] As preferred, in S1.4, the accumulative roll bonding is 6 passes, the single deformation amount is 50-70%, and the final layer number is 64 layers.
[0009] As preferred, the modified silicon carbide reinforcing agent is prepared by nitrogen-doped porous carbon-coated silicon carbide reinforcing agent; The preparation method of the modified silicon carbide reinforcing agent is as follows: Silicon carbide particles with a particle size of 15μm are placed in acetone and ultrasonically cleaned at a power of 200-300W for 20-30min; then, the cleaned silicon carbide is placed in a plasma reaction chamber, argon is introduced at a flow rate of 40-50sccm, the power is 130-150W, and the treatment time is 15-20min to obtain pretreated silicon carbide; The pretreated silicon carbide is added to a zinc acetate dihydrate solution and ultrasonically dispersed at a power of 100-200W for 10-15min; then, 2-methylimidazole solution is added and ultrasonically dispersed at a power of 100-200W for 5-10min; it is transferred to a polytetrafluoroethylene autoclave and reacted at 110-120℃ for 4-6h; after the reaction, it is centrifuged at a speed of 6000-8000rpm for 5-10min, and then washed with methanol for 2-3 times; it is vacuum dried at 50-60℃ for 10-12h to obtain a modified silicon carbide precursor; The modified silicon carbide precursor is placed in a tube furnace quartz boat, nitrogen is introduced at a speed of 200-300mL / min, and carbonization is carried out at 120-700℃ for 1-3h; after carbonization, it is naturally cooled to room temperature to obtain a modified silicon carbide reinforcing agent.
[0010] The outer layer of the modified silicon carbide reinforcing agent forms a dense carbon shell, and the surface energy is significantly reduced, thereby significantly improving the wettability with molten zinc; the inner layer SiC realizes energy buffering through the carbon cage transition layer, so that the overall interfacial energy is reduced, and the molten zinc can spontaneously spread and fill the micropores, eliminating the pores.
[0011] Preferably, the molar concentration of the zinc acetate dihydrate solution is 0.1 mol / L, and the molar concentration of the 2-methylimidazole solution is 0.8 mol / L. The mass ratio of the pretreated silicon carbide, the zinc acetate dihydrate solution and the 2-methylimidazole solution is 1:4.37:4.81.
[0012] Preferably, the modified ceria grain refiner is prepared by grafting vinyltrimethoxysilane on the surface after plasma activation. The preparation method of the modified ceria grain refiner is as follows: The pretreated ceria powder is subjected to plasma activation treatment; the activated ceria is added into a vinyltrimethoxysilane solution, and stirred at a speed of 400-500 rpm under a water bath at 50-60℃ for 1-2 h; after the reaction, centrifugation is performed at a speed of 4000-6000 rpm for 5-10 min, and then the activated ceria is washed with anhydrous ethanol for 2-3 times; vacuum drying is performed at 60℃ for 5-6 h to obtain the modified ceria grain refiner.
[0013] The surface of CeO2 is bombarded by plasma, which promotes the formation of Ce 3+ The proportion is increased, so that high-density oxygen vacancies are formed in the lattice, and these positively charged oxygen vacancies overcome the van der Waals force through long-range electrostatic repulsion, so that the agglomeration size is compressed; then vinyltrimethoxysilane (VTMS) is grafted on the surface, and the hydrophobic vinyl group (-CH=CH2) forms a molecular layer, which hinders the secondary agglomeration of particles through steric hindrance effect, and maintains the monodisperse state in the zinc melt.
[0014] Preferably, the plasma treatment uses a mixed gas of argon and oxygen, wherein the volume ratio of argon to oxygen is 4:1, the gas flow rate is 80-100 sccm, the treatment time is 5-10 min, and the discharge power is 200-300 W. The mass concentration of the vinyltrimethoxysilane solution is 1%-2%. The mass ratio of the activated ceria and the vinyltrimethoxysilane solution is 1:50.
[0015] Preferably, the wear-resistant lightweight zinc-based composite material containing a special grain refiner is prepared by using the above-mentioned preparation method of the wear-resistant lightweight zinc-based composite material containing a special grain refiner.
[0016] In another aspect, the application provides an application of the wear-resistant lightweight zinc-based composite material containing a special grain refiner, which is an application of the above-mentioned wear-resistant lightweight zinc-based composite material containing a special grain refiner in the preparation of mechanical manufacturing parts.
[0017] Compared with the prior art, the application has the following beneficial effects: 1、The special grain refiner containing wear-resistant lightweight zinc-based composite material preparation method and its application, by introducing nitrogen-doped porous carbon coated modified silicon carbide reinforcement, significantly improve the wettability and interface bonding strength with zinc alloy matrix, this structure not only effectively transfer load and inhibit crack propagation, thereby significantly improve the tensile strength, hardness and wear resistance of the composite material; in addition, the high hardness and low density characteristics of silicon carbide, can significantly improve the material rigidity after adding, while maintaining the lightweight advantage of the matrix.
[0018] 2、The special grain refiner containing wear-resistant lightweight zinc-based composite material preparation method and its application, the modified cerium oxide grain refiner is treated by plasma activation and silane grafting modification, which significantly enhances the surface active site, thereby improving its dispersibility and wettability in zinc alloy melt; this modification not only optimizes the grain refinement effect, but also reduces the grain boundary defects and stress concentration, thereby directly improving the wear resistance of the composite material; in addition, cerium oxide itself has good passivation performance, and the silane layer formed after modification can effectively delay the penetration of corrosion medium, further enhancing the corrosion resistance of the material. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0020] Firstly, the raw materials are pretreated, including the following: The operation steps of the modified silicon carbide reinforcement after drying: the modified silicon carbide reinforcement is placed in a vacuum drying box at a temperature of 250°C and a vacuum degree less than 10 -3 Pa for 2h; The operation steps of the pretreated cerium oxide powder: take CeO2 powder with a particle size of 20nm (purity ≥99.9%) and place it in a vacuum drying box at 120°C for 2h to ensure that the water content is less than 0.5wt%; sieve the powder through a 300 mesh sieve to eliminate hard agglomerates; finally, seal the treated powder in a desiccator and keep the environmental humidity ≤10%RH to prevent moisture absorption and oxidation; The zinc alloy is ZA35 zinc alloy, which mainly contains zinc (Zn), aluminum (Al), copper (Cu), magnesium (Mg) and other elements; among them, the content of aluminum is usually between 33.0%-37.0%, the content of copper is 0.75%-1.25%, the content of magnesium is in the range of 0.03%-0.06%, and the rest is zinc and unavoidable impurities.
[0021] Embodiment 1: A method for preparing a wear-resistant lightweight zinc-based composite material containing a special grain refiner, comprising the following steps: S1.1, the following raw materials are weighed respectively: 80 parts by weight of zinc alloy, 8 parts by weight of modified silicon carbide reinforcing agent, 0.5 parts by weight of modified cerium oxide grain refiner, and 0.5 parts by weight of sodium chloride-potassium chloride flux; S1.2, the zinc alloy is placed in a graphite crucible, the sodium chloride-potassium chloride composite flux is added, argon gas is introduced at a flow rate of 5 L / min, the temperature is raised to 550°C at a rate of 8°C / min and maintained, stirring is carried out at a speed of 200 rpm for 10 min to form a melt; S1.3, the modified cerium oxide grain refiner is ultrasonically dispersed into the melt at a power of 1.2 kW; the temperature of the melt is maintained at 550°C, the dried modified silicon carbide reinforcing agent is added, and stirring is carried out at a speed of 600 rpm for 30 min to obtain a mixed material; S1.4, when the temperature of the mixed material decreases to 480°C, casting is carried out using a pressure of 80 MPa; then, cumulative roll bonding is carried out for 6 passes, with a single deformation amount of 70% and a final layer number of 64 layers; after rolling, cooling is carried out to room temperature, annealing is carried out at 300°C for 20 min, and a wear-resistant lightweight zinc-based composite material containing a special grain refiner is obtained.
[0022] The preparation method of the modified silicon carbide reinforcing agent is as follows: Silicon carbide particles with a particle size of 15 μm are placed in acetone and ultrasonically cleaned at a power of 300 W for 30 min; then, the cleaned silicon carbide is placed in a plasma reaction chamber, argon gas is introduced at a flow rate of 50 sccm, the power is 140 W, and the treatment time is 20 min to obtain pretreated silicon carbide; The pretreated silicon carbide (the mass ratio of pretreated silicon carbide, zinc acetate dihydrate solution, and 2-methylimidazole solution is 1:4.37:4.81) is added to a 0.1 mol / L zinc acetate dihydrate solution, ultrasonically dispersed at a power of 200 W for 15 min; then, a 0.8 mol / L 2-methylimidazole solution is added, ultrasonically dispersed at a power of 200 W for 10 min; transferred to a polytetrafluoroethylene autoclave, reacted at 120°C for 6 h; after reaction, centrifuged at a speed of 8000 rpm for 5 min, washed with methanol for 3 times; vacuum dried at 60°C for 12 h to obtain a modified silicon carbide precursor; The modified silicon carbide precursor is placed in a tube furnace quartz boat, nitrogen gas is introduced at a speed of 300 mL / min, and carbonization is carried out at 650°C for 3 h; after carbonization, natural cooling is carried out to room temperature to obtain a modified silicon carbide reinforcing agent.
[0023] The preparation method of the modified cerium oxide grain refiner is as follows: The pretreated cerium oxide powder is subjected to plasma activation treatment, argon and oxygen mixed gas (volume ratio 4:1) is used, the gas flow rate is 80 sccm, the treatment time is 10 min, and the discharge power is 300 W; the activated cerium oxide is mixed with a 2% vinyltrimethoxysilane solution (mass ratio 1:50), stirred at 500 rpm in a 60°C water bath for 2 h; after reaction, centrifugation is performed at 6000 rpm for 10 min, then washed with anhydrous ethanol for 3 times, and finally dried at 60°C under vacuum for 6 h to obtain the modified cerium oxide grain refiner.
[0024] Example 2: A preparation method of a wear-resistant lightweight zinc-based composite material containing a special grain refiner, comprising the following steps: S1.1, respectively, the following raw materials are weighed: zinc alloy 90 parts by weight, modified silicon carbide reinforcing agent 12 parts by weight, modified cerium oxide grain refiner 0.8 parts by weight, and sodium chloride-potassium chloride flux 1.0 parts by weight; S1.2, the zinc alloy is placed in a graphite crucible, the sodium chloride-potassium chloride composite flux is added, argon is introduced at a flow rate of 5 L / min, the temperature is increased to 550°C at a rate of 8°C / min and maintained; stirred at a speed of 200 rpm for 10 min to form a melt; S1.3, the modified cerium oxide grain refiner is ultrasonically dispersed into the melt at a power of 1.2 kW; the melt temperature is maintained at 550°C, the dried modified silicon carbide reinforcing agent is added, and stirred at a speed of 600 rpm for 30 min to obtain a mixed material; S1.4, when the temperature of the mixed material decreases to 480°C, casting is carried out by using a pressure of 80 MPa; then through cumulative roll bonding, the cumulative roll bonding is 6 passes, the single deformation amount is 70%, and the final layer number is 64 layers; after rolling, it is cooled to room temperature, and then annealed at 300°C for 20 min to obtain a wear-resistant lightweight zinc-based composite material containing a special grain refiner.
[0025] The preparation method of the modified silicon carbide reinforcing agent is as follows: The silicon carbide particles with a particle size of 15 μm are placed in acetone and ultrasonically cleaned at a power of 300 W for 30 min; then the cleaned silicon carbide is placed in a plasma reaction chamber, argon gas is introduced at a flow rate of 50 sccm, the power is 140 W, and the treatment time is 20 min to obtain pretreated silicon carbide; The pretreated silicon carbide (mass ratio of pretreated silicon carbide, zinc acetate dihydrate solution and 2-methylimidazole solution is 1:4.37:4.81) is added into a zinc acetate dihydrate solution with a molar concentration of 0.1 mol / L, and ultrasonic dispersion is performed at a power of 200 W for 15 min; then a 2-methylimidazole solution with a molar concentration of 0.8 mol / L is added, and ultrasonic dispersion is performed at a power of 200 W for 10 min; then the mixture is transferred into a polytetrafluoroethylene autoclave, and reaction is performed at 120℃ for 6 h; after the reaction, centrifugation is performed at a speed of 8000 rpm for 5 min, and then methanol is used for washing 3 times; vacuum drying is performed at 60℃ for 12 h, and a modified silicon carbide precursor is obtained. The modified silicon carbide precursor is placed in a tube furnace quartz boat, nitrogen gas is introduced at a speed of 300 mL / min, and carbonization is performed at 650℃ for 3 h; after the carbonization, natural cooling is performed to room temperature, and a modified silicon carbide reinforcing body is obtained.
[0026] The preparation method of the modified cerium oxide grain refiner is as follows: The pretreated cerium oxide powder is subjected to plasma activation treatment, argon and oxygen mixed gas (volume ratio 4:1) is used, the gas flow rate is 80 sccm, the treatment time is 10 min, and the discharge power is 300 W; the activated cerium oxide is mixed with a vinyltrimethoxysilane solution with a mass concentration of 2% (mass ratio 1:50), stirring is performed at 500 rpm in a 60℃ water bath for 2 h; after the reaction, centrifugation is performed at 6000 rpm for 10 min, then anhydrous ethanol is used for washing 3 times, and finally vacuum drying is performed at 60℃ for 6 h, and a modified cerium oxide grain refiner is obtained.
[0027] Embodiment 3: A preparation method of a wear-resistant lightweight zinc-based composite material containing a special grain refiner, comprising the following steps: S1.1, the following raw materials are weighed according to the weight parts respectively: zinc alloy 100 weight parts, modified silicon carbide reinforcing body 15 weight parts, modified cerium oxide grain refiner 1.0 weight parts and sodium chloride-potassium chloride flux 1.5 weight parts; S1.2, the zinc alloy is placed in a graphite crucible, the sodium chloride-potassium chloride composite flux is added, argon gas is introduced at a flow rate of 5 L / min, the temperature is increased to 550℃ at a speed of 8℃ / min and maintained, and stirring is performed at a speed of 200 rpm for 10 min to form a melt; S1.3, the modified cerium oxide grain refiner is ultrasonically dispersed into the melt at a power of 1.2 kW; the temperature of the melt is maintained at 550℃, the dried modified silicon carbide reinforcing body is added, and stirring is performed at a speed of 600 rpm for 30 min to obtain a mixed material; S1.4, when the temperature of the mixed material drops to 480℃, casting is carried out by using a pressure of 80 MPa; then, through accumulative roll-bonding, the accumulative roll-bonding is 6 passes, the single deformation amount is 70%, and the final layer number is 64 layers; after rolling, cooling is carried out to room temperature, annealing is carried out at 300℃ for 20 min, and a wear-resistant lightweight zinc-based composite material containing a special grain refiner is obtained.
[0028] The preparation method of the modified silicon carbide reinforcing agent is as follows: Silicon carbide particles with a particle size of 15 μm are placed in acetone and ultrasonically cleaned at a power of 300 W for 30 min; then, the cleaned silicon carbide is placed in a plasma reaction chamber, argon gas is introduced at a flow rate of 50 sccm, the power is 140 W, and the treatment is carried out for 20 min to obtain pretreated silicon carbide; The pretreated silicon carbide (the mass ratio of pretreated silicon carbide, zinc acetate dihydrate solution and 2-methyl imidazole solution is 1:4.37:4.81) is added to a 0.1 mol / L zinc acetate dihydrate solution, ultrasonically dispersed at a power of 200 W for 15 min; then, a 0.8 mol / L 2-methyl imidazole solution is added, ultrasonically dispersed at a power of 200 W for 10 min; transferred to a polytetrafluoroethylene autoclave, reacted at 120℃ for 6 h; after the reaction, centrifuged at a speed of 8000 rpm for 5 min, washed with methanol for 3 times; vacuum dried at 60℃ for 12 h to obtain a modified silicon carbide precursor; The modified silicon carbide precursor is placed in a tube furnace quartz boat, nitrogen gas is introduced at a speed of 300 mL / min, and carbonization is carried out at 650℃ for 3 h; after carbonization, natural cooling is carried out to room temperature to obtain a modified silicon carbide reinforcing agent.
[0029] The preparation method of the modified cerium oxide grain refiner is as follows: The pretreated cerium oxide powder is subjected to plasma activation treatment, argon and oxygen mixed gas (volume ratio 4:1) is used, the gas flow rate is 80 sccm, the treatment time is 10 min, and the discharge power is 300 W; the activated cerium oxide is mixed with a 2% vinyltrimethoxysilane solution (mass ratio 1:50), stirred at 500 rpm in a 60℃ water bath for 2 h; after the reaction, centrifuged at 6000 rpm for 10 min, washed with anhydrous ethanol for 3 times, and finally vacuum dried at 60℃ for 6 h to obtain a modified cerium oxide grain refiner.
[0030] Example 4: A preparation method of a wear-resistant lightweight zinc-based composite material containing a special grain refiner, comprising the following steps: S1.1, the following raw materials are weighed according to the weight parts respectively: zinc alloy 90 weight parts, modified silicon carbide reinforcing agent 5 weight parts, modified cerium oxide grain refiner 0.8 weight parts, and sodium chloride-potassium chloride flux 1.0 weight parts; S1.2, the zinc alloy is placed in a graphite crucible, sodium chloride-potassium chloride composite flux is added, argon is introduced at a flow rate of 5 L / min, the temperature is increased to 550°C at a rate of 8°C / min and maintained; stirring is performed at a speed of 200 rpm for 10 min to form a melt; S1.3, the modified cerium oxide grain refiner is ultrasonically dispersed into the melt at a power of 1.2 kW; the melt temperature is maintained at 550°C, dried modified silicon carbide reinforcing agent is added, and stirring is performed at a speed of 600 rpm for 30 min to obtain a mixed material; S1.4, when the temperature of the mixed material decreases to 480°C, casting is performed using a pressure of 80 MPa; then, cumulative roll bonding is performed, with 6 passes, a single deformation amount of 70%, and a final layer number of 64 layers; after rolling, cooling is performed to room temperature, annealing is performed at 300°C for 20 min, and a wear-resistant lightweight zinc-based composite material containing a special grain refiner is obtained.
[0031] The preparation method of the modified silicon carbide reinforcing agent is as follows: Silicon carbide particles with a particle size of 15 μm are placed in acetone and ultrasonically cleaned at a power of 300 W for 30 min; then, the cleaned silicon carbide is placed in a plasma reaction chamber, argon is introduced at a flow rate of 50 sccm, the power is 140 W, and the treatment is performed for 20 min to obtain pretreated silicon carbide; The pretreated silicon carbide (the mass ratio of pretreated silicon carbide, zinc acetate dihydrate solution, and 2-methylimidazole solution is 1:4.37:4.81) is added to a 0.1 mol / L zinc acetate dihydrate solution, ultrasonically dispersed at a power of 200 W for 15 min; then, a 0.8 mol / L 2-methylimidazole solution is added, ultrasonically dispersed at a power of 200 W for 10 min; transferred to a polytetrafluoroethylene autoclave, reacted at 120°C for 6 h; after the reaction, centrifuged at a speed of 8000 rpm for 5 min, washed with methanol 3 times; vacuum dried at 60°C for 12 h to obtain a modified silicon carbide precursor; The modified silicon carbide precursor is placed in a tube furnace quartz boat, nitrogen is introduced at a rate of 300 mL / min, and carbonization is performed at 650°C for 3 h: after carbonization, natural cooling is performed to room temperature to obtain a modified silicon carbide reinforcing agent.
[0032] The preparation method of the modified cerium oxide grain refiner is as follows: The pretreated cerium oxide powder is subjected to plasma activation treatment, argon and oxygen mixed gas (volume ratio 4:1) is used, the gas flow rate is 80 sccm, the treatment time is 10 min, and the discharge power is 300 W; the activated cerium oxide is mixed with a 2% vinyltrimethoxysilane solution (mass ratio 1:50), stirred at 500 rpm in a 60°C water bath for 2 h; after reaction, centrifugation is performed at 6000 rpm for 10 min, then washed with anhydrous ethanol for 3 times, and finally dried at 60°C under vacuum for 6 h, to obtain the modified cerium oxide grain refiner.
[0033] Example 5: A method for preparing a wear-resistant lightweight zinc-based composite material containing a special grain refiner, comprising the following steps: S1.1, respectively, the following raw materials are weighed: zinc alloy 90 parts by weight, modified silicon carbide reinforcing agent 12 parts by weight, modified cerium oxide grain refiner 0.1 parts by weight, and sodium chloride-potassium chloride flux 1.0 parts by weight; S1.2, the zinc alloy is placed in a graphite crucible, the sodium chloride-potassium chloride composite flux is added, argon is introduced at a flow rate of 5 L / min, the temperature is increased to 550°C at a rate of 8°C / min and maintained; stirred at a speed of 200 rpm for 10 min to form a melt; S1.3, the modified cerium oxide grain refiner is ultrasonically dispersed into the melt at a power of 1.2 kW; maintain the melt temperature at 550°C, add the dried modified silicon carbide reinforcing agent, and stir at a speed of 600 rpm for 30 min to obtain a mixed material; S1.4, when the temperature of the mixed material decreases to 480°C, casting is performed using a pressure of 80 MPa; then through cumulative roll bonding, cumulative roll bonding is 6 passes, single deformation amount is 70%, and the final layer number is 64 layers; after rolling, cool to room temperature, and anneal at 300°C for 20 min to obtain a wear-resistant lightweight zinc-based composite material containing a special grain refiner.
[0034] The preparation method of the modified silicon carbide reinforcing agent is as follows: The silicon carbide particles with a particle size of 15 μm are placed in acetone and ultrasonically cleaned at a power of 300 W for 30 min; then the cleaned silicon carbide is placed in a plasma reaction chamber, argon gas is introduced at a flow rate of 50 sccm, the power is 140 W, and the treatment time is 20 min to obtain pretreated silicon carbide; The pretreated silicon carbide (mass ratio of the pretreated silicon carbide, zinc acetate dihydrate solution and 2-methylimidazole solution is 1:4.37:4.81) is added into a zinc acetate dihydrate solution with a molar concentration of 0.1 mol / L, and is ultrasonically dispersed at a power of 200 W for 15 min; then a 2-methylimidazole solution with a molar concentration of 0.8 mol / L is added, and is ultrasonically dispersed at a power of 200 W for 10 min; then it is transferred into a polytetrafluoroethylene autoclave, and is reacted at 120 ℃ for 6 h; after the reaction, it is centrifuged at a speed of 8000 rpm for 5 min, and is washed with methanol for 3 times; and then it is vacuum dried at 60 ℃ for 12 h, to obtain a modified silicon carbide precursor; The modified silicon carbide precursor is placed in a tube furnace quartz boat, nitrogen is introduced at a speed of 300 mL / min, and carbonization is performed at 650 ℃ for 3 h; after the carbonization, it is naturally cooled to room temperature, to obtain a modified silicon carbide reinforcing agent.
[0035] The preparation method of the modified cerium oxide grain refiner is as follows: The pretreated cerium oxide powder is subjected to plasma activation treatment, argon and oxygen mixed gas (volume ratio 4:1) is used, the gas flow rate is 80 sccm, the treatment time is 10 min, and the discharge power is 300 W; the activated cerium oxide is mixed with a vinyltrimethoxysilane solution with a mass concentration of 2% (mass ratio 1:50), and is stirred at 500 rpm in a 60 ℃ water bath for 2 h; after the reaction, it is centrifuged at 6000 rpm for 10 min, and is washed with anhydrous ethanol for 3 times; and finally it is vacuum dried at 60 ℃ for 6 h, to obtain a modified cerium oxide grain refiner.
[0036] Comparative Example 1: The method of Example 2 is used in a method for preparing a wear-resistant lightweight zinc-based composite material containing a special grain refiner, and a modified silicon carbide reinforcing agent is not used, but a silicon carbide is directly used.
[0037] Comparative Example 2: The method of Example 2 is used in a method for preparing a wear-resistant lightweight zinc-based composite material containing a special grain refiner, and a modified cerium oxide grain refiner is not used, but a cerium oxide grain refiner is directly used.
[0038] By adding a modified silicon carbide reinforcing agent and a modified cerium oxide grain refiner in a method for preparing a wear-resistant lightweight zinc-based composite material containing a special grain refiner, and by testing the performance index and test standard of the obtained wear-resistant lightweight zinc-based composite material containing a special grain refiner, the following results are obtained: The cutting composite material is a 30x10mm cylindrical sample; the counter-abrasion part is a GCr15 bearing steel ring with a hardness of HRC60±2; the test parameters are set as follows: load 200N (simulating medium-high stress working conditions), rotation speed 400rpm (corresponding to a sliding speed of 0.42m / s), test time 30min (total sliding distance 756m); the precision electronic balance (accuracy 0.1mg) is used to weigh before and after the test and the wear rate is calculated by formula; a lower wear rate indicates that the material surface has a strong anti-stripping ability, effectively inhibiting abrasive wear and adhesive wear.
[0039] A 25x10x2mm layered composite material sample is prepared, a universal material testing machine is used in the test, a three-point bending fixture is used, the span is 20mm, the loading speed is set to 1mm / min, the load-displacement curve is recorded, and the interfacial shear strength of the composite material is calculated; a higher interfacial shear strength helps to delay the initiation of cracks, so that the composite material maintains good performance under stress. 3
[0040] The wear-resistant lightweight zinc-based composite material containing the special grain refiner prepared in the above examples 1-5 and comparative examples 1-2 is tested according to the above standards, and the data obtained are shown in Table 1: Table 1 Performance data of the wear-resistant lightweight zinc-based composite material of examples 1-5 and comparative examples 1-2
[0041] As can be seen from examples 1-3 and 4, when the weight of the modified silicon carbide reinforcing agent in the wear-resistant lightweight zinc-based composite material containing the special grain refiner is increased while other components remain unchanged, the wear rate of the composite material first decreases and then increases, and the interfacial shear strength first increases and then decreases; the modified silicon carbide reinforcing agent forms a continuous hard skeleton, effectively resisting the cutting and furrowing action of abrasive particles, thereby significantly reducing the wear rate; in addition, the nitrogen-doped porous carbon on the surface of the modified silicon carbide reinforcing agent releases a graphene-like carbon layer during friction, further reducing the friction coefficient; after the silicon carbide reinforcing agent is coated with nitrogen-doped porous carbon, the surface roughness increases, forming a mechanical interlocking structure with the zinc matrix, enhancing the interfacial bonding.
[0042] It can be seen from Examples 1-3 and Example 5 that when the weight of the modified cerium oxide grain refiner is increased in the wear-resistant lightweight zinc-based composite material containing a special grain refiner, the wear rate of the composite material first decreases and then increases, and the interfacial shear strength first increases and then decreases; the silane groups (such as vinyl trimethoxysilane) grafted on the surface of the modified cerium oxide enhance its dispersibility and wettability in the zinc melt, thereby forming more nucleation sites in a unit volume; as a high-efficiency heterogeneous core, CeO2 promotes the nucleation of grains, reduces the grain size, and significantly increases the grain boundary density; the fine-grained structure effectively hinders dislocation slip and crack propagation, reduces stress concentration, and thus improves the ability of the material surface to withstand local load; in addition, plasma activation causes active groups such as hydroxyl groups on the surface of CeO2, and after silane grafting, an organic-inorganic hybrid layer is formed, which forms a covalent bond with the zinc matrix, significantly enhancing the interfacial bonding force.
[0043] According to the above test experiments, Example 2 is taken as the optimal example. It can be seen from the comparison between Example 2 and Comparative Example 1 that when the modified silicon carbide reinforcing agent is not used and silicon carbide is directly used, the wear rate of the composite material significantly increases and the interfacial shear strength significantly decreases; the original silicon carbide surface has high inertness and poor wettability with the zinc matrix, which easily forms micropores and gaps at the interface, thereby weakening the interfacial bonding force; in contrast, the modified silicon carbide forms a chemical bond with the matrix through a nitrogen-doped porous carbon layer, significantly enhancing the interfacial bonding force, while the unmodified silicon carbide only relies on mechanical anchoring, and the interfacial bonding is weak; in addition, silicon carbide particles are easily detached from the matrix under weak interfacial conditions, forming hard abrasive particles that further scratch the material surface.
[0044] It can be seen from the comparison between Example 2 and Comparative Example 2 that when the modified cerium oxide grain refiner is not used and the cerium oxide grain refiner is directly used, the wear rate of the composite material significantly increases and the interfacial shear strength significantly decreases; the unmodified cerium oxide has low surface activity due to the lack of plasma activation and silane grafting, and easily agglomerates in the zinc melt; the agglomerates form hard inclusions in the matrix, which become interfacial stress concentration points and induce microcracks; the unmodified cerium oxide has poor dispersibility and low heterogeneous nucleation efficiency, resulting in an increase in the grain size of the zinc matrix, which makes the material hardness decrease and the abrasive particles more easily embedded on the surface, accelerating the surface plowing.
[0045] The above shows and describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited to the above-mentioned embodiments, and the above-mentioned embodiments and descriptions in the specification are only preferred examples of the present application and are not intended to limit the present application. Various changes and improvements can be made to the present application without departing from the spirit and scope of the present application, and these changes and improvements all fall within the scope of the claimed present application. The scope of protection of the present application is defined by the appended claims and their equivalents.
Claims
1. A process for the production of wear resistant lightweight zinc based composite material containing special grain refiner, characterized by, The method comprises the following steps: S1.1, respectively, take the following raw materials: zinc alloy, modified silicon carbide reinforcement, modified cerium oxide grain refiner and sodium chloride-potassium chloride complex flux; S1.2, the zinc alloy is placed in a graphite crucible, the sodium chloride-potassium chloride complex flux is added, argon is introduced, the temperature is raised to 550-560℃ and is kept constant; stirring at a speed of 150-200 rpm for 10-15 min to form a melt; S1.3, the modified cerium oxide grain refiner is ultrasonically dispersed into the melt at a power of 1.0-1.2 kW; the temperature of the melt is maintained at 545-555℃, the dried modified silicon carbide reinforcement is added, and stirring is carried out at a speed of 600-800 rpm for 20-30 min to obtain a mixed material; S1.4, when the temperature of the mixed material decreases to 460-480℃, casting is carried out by using a pressure of 60-80 MPa; then, through cumulative roll bonding, after rolling, cooling to room temperature, and annealing at 300℃ for 20 min, a wear-resistant lightweight zinc-based composite material containing a special grain refiner is obtained.
2. A process for the production of wear resistant lightweight zinc based composite containing special grain refiner as claimed in claim 1 wherein, In S1.1, the following raw materials are weighed by weight parts: 80-100 parts by weight of zinc alloy, 8-15 parts by weight of modified silicon carbide reinforcement, 0.5-1.0 parts by weight of modified cerium oxide grain refiner, and 0.5-1.5 parts by weight of sodium chloride-potassium chloride flux.
3. The method of producing wear resistant lightweight zinc based composite material containing special grain refiner according to claim 1, characterized in that, In S1.2, the flow rate of argon is 3-5 L / min; the temperature is raised at a rate of 8-10℃ / min.
4. The method of producing wear resistant lightweight zinc based composite material containing special grain refiner according to claim 1, characterized in that, In S1.4, the cumulative roll bonding is 6 passes, the single deformation amount is 50-70%, and the final layer number is 64 layers.
5. The method of producing wear resistant lightweight zinc based composite material containing special grain refiner according to claim 2, characterized in that, The modified silicon carbide reinforcement is prepared by nitrogen-doped porous carbon-coated silicon carbide reinforcement; The preparation method of the modified silicon carbide reinforcement is as follows: The silicon carbide particles with a particle size of 15 μm are placed in acetone and ultrasonically cleaned at a power of 200-300 W for 20-30 min; then, the cleaned silicon carbide is placed in a plasma reaction chamber, argon is introduced at a flow rate of 40-50 sccm, the power is 130-150 W, and the treatment time is 15-20 min to obtain pretreated silicon carbide; The pretreated silicon carbide is added to a zinc acetate dihydrate solution, ultrasonically dispersed at a power of 100-200 W for 10-15 min, then 2-methylimidazole solution is added, ultrasonically dispersed at a power of 100-200 W for 5-10 min, transferred to a polytetrafluoroethylene autoclave, and reacted at 110-120℃ for 4-6 h; after the reaction, centrifugation is carried out at a speed of 6000-8000 rpm for 5-10 min, and then washed with methanol for 2-3 times; vacuum drying at 50-60℃ for 10-12 h to obtain a modified silicon carbide precursor; The modified silicon carbide precursor is placed in a tubular furnace quartz boat, nitrogen is introduced at a rate of 200-300 mL / min, and carbonization is carried out at 120-700℃ for 1-3 h; after carbonization, natural cooling to room temperature is carried out to obtain a modified silicon carbide reinforcement.
6. The method of producing wear resistant lightweight zinc based composite material containing special grain refiner according to claim 5, characterized in that, The molar concentration of the zinc acetate dihydrate solution is 0.1 mol / L, and the molar concentration of the 2-methylimidazole solution is 0.8 mol / L; The mass ratio of the pretreated silicon carbide, zinc acetate dihydrate solution and 2-methyl imidazole solution is 1:4.37:4.
81.
7. The process for making wear-resistant lightweight zinc-based composite containing special grain refiner as claimed in claim 2 wherein, The modified cerium oxide grain refiner is prepared by grafting vinyl trimethoxysilane on the surface after plasma activation; The preparation method of the modified cerium oxide grain refiner is as follows: The pretreated cerium oxide powder is subjected to plasma activation treatment; the activated cerium oxide is added into a vinyl trimethoxysilane solution, and stirred at a speed of 400-500 rpm under a water bath at 50-60 ℃ for 1-2 h; after the reaction, centrifugation is performed at a speed of 4000-6000 rpm for 5-10 min, and then washing is performed 2-3 times with anhydrous ethanol; vacuum drying is performed at 60 ℃ for 5-6 h to obtain the modified cerium oxide grain refiner.
8. The method of producing wear resistant lightweight zinc based composite material containing special grain refiner according to claim 7, characterized in that, The plasma treatment adopts a mixed gas of argon and oxygen, wherein the volume ratio of argon and oxygen is 4:1, the gas flow rate is 80-100 sccm, the treatment time is 5-10 min, and the discharge power is 200-300 W; The mass concentration of the vinyl trimethoxysilane solution is 1%-2%; The mass ratio of the activated cerium oxide and the vinyl trimethoxysilane solution is 1:
50.
9. A wear-resistant lightweight zinc-based composite material containing a special grain refiner, which is prepared by using the preparation method of the wear-resistant lightweight zinc-based composite material containing a special grain refiner according to any one of claims 1-8.
10. Application of a wear-resistant lightweight zinc-based composite material containing a special grain refiner, which is the application of the wear-resistant lightweight zinc-based composite material containing a special grain refiner according to claim 9 in the preparation of mechanical manufacturing parts.
Citation Information
Patent Citations
Preparation method of silicon carbide enhanced high aluminum zinc base composite material
CN107739870A
Preparation method of particle enhanced high aluminum zinc based composite material
CN108517430A
Casting anti-friction and abrasion-resistant high aluminum zinc-based composite material and preparation method thereof
CN109778014A
Nano-silicon carbide particle reinforced zinc-aluminum-based composite material and preparation method thereof
CN109881046A
The aluminum alloys containing Zn having excellentformability and anti-abrasion, and the method formanufacturing the same
KR1020060071515A